2018
DOI: 10.1186/s12889-018-5042-4
|View full text |Cite
|
Sign up to set email alerts
|

Tools for a systematic appraisal of integrated community-based approaches to prevent childhood obesity

Abstract: BackgroundEvaluation and monitoring methods are often unable to identify crucial elements of success or failure of integrated community-wide approaches aiming to tackle childhood overweight and obesity, yet difficult to determine in complex programmes. Therefore, we aimed to systematically appraise strengths and weaknesses of such programmes and to assess the usefulness of the appraisal tools used.MethodsTo identify strengths and weaknesses of the integrated community-based approaches two tools were used: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Based on such evidence, social ecological approaches have been recommended to prevent and control childhood obesity (Mantziki et al. ). Williams () suggests the associations between child weight‐regulating behaviours and multiple environmental influences should be examined within an ecological framework to guide development of effective programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on such evidence, social ecological approaches have been recommended to prevent and control childhood obesity (Mantziki et al. ). Williams () suggests the associations between child weight‐regulating behaviours and multiple environmental influences should be examined within an ecological framework to guide development of effective programs.…”
Section: Introductionmentioning
confidence: 99%
“…Grow et al's (2010) multilevel analysis of risk factors for obesity in children from 6 to 18 years noted social disadvantage in both a child's immediate household and their neighbourhood. Based on such evidence, social ecological approaches have been recommended to prevent and control childhood obesity (Mantziki et al 2018). Williams (2011) suggests the associations between child weight-regulating behaviours and multiple environmental influences should be examined within an ecological framework to guide development of effective programs.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of integrated approaches such as EPODE and JOGG is still in its infancy, and is complicated by often poor- to moderate-quality monitoring and evaluation [ 37 ] due to a lack of motivation, resources, time, and knowledge [ 38 , 39 ]. Furthermore, target groups are often not thoroughly assessed prior to designing the intervention, which makes it more difficult to reach and engage with the target group and achieve the intended change [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation report concluded that after EPODE interventions, lower SES groups improved their behaviour compared to the other socio‐economic groups. However, the authors of a systematic evaluation of integrated community‐based programmes across Europe using the EPODE methodology identified limitations in the design of some approaches (Mantziki et al ). These included limited analysis of the specific needs of the target group ( e.g.…”
Section: Community‐wide Interventions Aiming To Reduce Childhood Obesmentioning
confidence: 99%